Factors influencing the integration of ICT in the teaching and learning of O’ level geography in Chirumanzu district - Mangwaya, Batsirai (Midlands State University, 2018)
The purpose of the study was to find the factors influencing the integration of ICT in the teaching and learning of O’ level Geography in Chirumanzu District. It was significant for the researcher to carry out the study because there is need for provision of relevant technological equipment to enable students to develop skills that are essential for a technological age. The qualitative research design was used which allowed the generation of empirical data using thematic analysis approach. The data generating instruments used were the interview and observation schedule as well as the document analysis. A sample of three teachers and three heads of departments was purposively selected on the bases of the availability of computers. The findings from this study revealed that teachers were qualified and experienced enough to teach O’ level Geography. However shortage of teaching and learning resources and negative attitude portrayed by the teachers towards the integration of ICT are the major contributing factors causing slow integration. The researcher recommends that schools should carry out fundraising activities in order to avail resources for the integration of ICT in the teaching and learning of Geography. Workshops or staff development sessions should be carried out so that teachers are well informed and equipped to minimize their negative attitudes